If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2) * y + 1 = (2) * y + 3 Multiply 2 * 2 4y + 1 = (2) * y + 3 Reorder the terms: 1 + 4y = (2) * y + 3 Reorder the terms: 1 + 4y = 3 + 2y Solving 1 + 4y = 3 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 1 + 4y + -2y = 3 + 2y + -2y Combine like terms: 4y + -2y = 2y 1 + 2y = 3 + 2y + -2y Combine like terms: 2y + -2y = 0 1 + 2y = 3 + 0 1 + 2y = 3 Add '-1' to each side of the equation. 1 + -1 + 2y = 3 + -1 Combine like terms: 1 + -1 = 0 0 + 2y = 3 + -1 2y = 3 + -1 Combine like terms: 3 + -1 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| 9x-8=16x+27 | | 12x+2.6=6.8x | | 54=3y+x | | 54=3x+y | | 2(x+9)=30+18 | | (19+3)2=x | | 5/4k=5 | | 54-3(45)= | | 5-2(4x-2)+2x= | | xa+5=7x+b | | -9(x+4)+2x+5=6x+11 | | Y=3*X+2 | | 3(45)+x+6(45)+4x=180 | | 4xy+5xy-3xz-2xy+xy+3xz= | | 8x+6-9x=2-y-15 | | 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 | | 5b-3/3b-4b+1/5b | | .2y+.5x=4.05 | | 2/3n=-18 | | -12=.5x+x | | 3y+x=54 | | 2(x+8)=30+18 | | 3x+y=54 | | 4x+4x=50 | | -12=6+1y |